Rising from the mailroom to the boardroom : unique insights for governance, risk, compliance and audit leaders - Turner, Bruce R. (Internal audit and IT audit, 2021)
Boards and business leaders expect their key advisors to deliver fresh insights, and increasingly expect them to demonstrate foresight. To achieve what is expected, it is crucial to understand the dynamics of conversations in the boardroom and around the audit committee table. This book provides those unique perspectives. The journey from the 'mailroom to the boardroom' follows the story of a young banker who moved into the internal auditing profession as part of the 'new breed', then rose through the ranks into senior leadership and chief audit executive roles, before assuming audit committee and board roles that had an immense influence on governance, risk, compliance, and audit professionals. Success does not always follow a smooth and uneventful trajectory, and this story reflects insights from both the ups and the downs of the journey. Each chapter shares insights, better practices, case studies, practical examples, and real-life challenges and draws them together into 101 building blocks, each one providing crucial career-long learnings. The storytelling provides insights to people at all levels on the importance of positioning oneself to step into leadership roles, helps them understand how to evaluate and pursue potential career growth opportunities, provides tips on how to holistically manage and advance their career, and inspires higher-level thinking that enhances governance, risk, compliance and audit practices.